Strong convergence theorem by shrinking projection method for new nonlinear mappings in Banach spaces and applications. (3rd April 2017) - Takahashi, Wataru; Wen, Ching-Feng; Yao, Jen-Chih
Abstract: In this paper, we introduce the concept of a new nonlinear mapping called demigeneralized in a Banach space. Then, using the shrinking projection method, we prove a strong convergence theorem for finding a common fixed point for a family of the new nonlinear mappings in a Banach space. We apply this result to obtain new strong convergence theorems in a Hilbert space and a Banach space, respectively.